Journalism History, Web Archives, and New Methods for Understanding the Evolution of Digital Journalism. Issue 9 (21st October 2018) - Weber, Matthew S.; Napoli, Philip M.
Abstract : Archived webpages are a critical source of data for understanding the current state of the news media industry, as well as how the industry has changed over time. Dramatic changes in the news media industry in recent decades have occurred in tandem with the evolution on the Web. Archived webpages are valuable records for understanding and analyzing how newspaper companies have adapted to technological changes such as social media feeds and sharing of news content via Twitter. This article outlines a methodological approach to utilizing Web archives as a means of examining change in the news media industry. Researchers have developed new tools to improve researcher access to archived Web data in order to advance studies of the Web, and to enable the tracking of changes in news media as they emerge over time. A case study examining local news in the United States is used to illustrate the methodological challenges and promise of working with these data, highlighting the power and potential of Web archives for journalism research. Finally, the closing sections discuss challenges associated with the scale and scope of archived Web data and point to new areas for future research.